2006
DOI: 10.3347/kjp.2006.44.3.239
|View full text |Cite
|
Sign up to set email alerts
|

In vitro protoscolicidal effects of hypertonic glucose on protoscolices of hydatid cyst

Abstract: To evaluate the protoscolicidal effects of various concentrations of hypertonic glucose, live protoscolices of sheep were exposed to 10%, 15%, 25% and 50% glucose solutions. Cetrimide (0.5%), silver nitrate (0.5%) and hypertonic saline (20%) were used as positive controls, while physiological saline was used as a negative control. After 1, 2 and 5 min, the protoscolicidal effects were determined by 1% eosin. A 25% glucose solution had no significant protoscolicidal effect. However, a 50% glucose solution revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Hypertonic glucose was used as a protoscolicidal agent in pericardial hydatid cyst by Ferini et al [6] and also for an in vitro study evaluating the protoscolicidal effects of various concentration of this solution by Hosseini et al [7]. In our study, 50% dextrose solution revealed higher protoscolicidal effect than 20% silver GRAPHIC 1 nitrate in the first 5 min, but it showed a weaker effect than 20% silver nitrate in 20 min.…”
Section: Discussionmentioning
confidence: 67%
“…Hypertonic glucose was used as a protoscolicidal agent in pericardial hydatid cyst by Ferini et al [6] and also for an in vitro study evaluating the protoscolicidal effects of various concentration of this solution by Hosseini et al [7]. In our study, 50% dextrose solution revealed higher protoscolicidal effect than 20% silver GRAPHIC 1 nitrate in the first 5 min, but it showed a weaker effect than 20% silver nitrate in 20 min.…”
Section: Discussionmentioning
confidence: 67%
“…For this reason, scolocidal agents such as hypertonic saline or silver nitrate are often used for the killing of protoscoleces inside the cyst during the surgery. Different protoscolicidal agents such as 70%-95% ethanol, 15%-20% hypertonic saline solution and 0.5% cetrimide solution or even hypertonic glucose have been used both in vivo and in vitro with variety of effects [3,13]. It has been suggested that more experimental studies and clinical observations are urgently needed for evaluating the efficacy and safety of protosclolicides [9].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro evaluation of protoscolicidal effects of hypertonic glucose on protoscolices of hydatid cyst using 10%, 25%, and 50% glucose solutions showed that protoscolicidal effect of 50% glucose solution was higher than 0.5% silver nitrate and weaker than 0.5% cetrimide, but the effect was comparable with that of 20% hypertonic saline solution [9].…”
Section: Introductionmentioning
confidence: 91%
“…So, in treatment attempts, surgeons utilize several protoscolicidal agents such as cetrimide, silver nitrate, hypertonic saline, and povidone iodine [7,8]. The 0.5% silver nitrate, 0.5% cetrimide, and 20% hypertonic saline solutions are considered as old protoscolicidal agents, but 15% and 25% dextrose solutions are the new ones [9]. The use of silver nitrate is more popular in Iran, but hypertonic saline is still the solution of choice in many countries [7].…”
Section: Introductionmentioning
confidence: 99%